The African art collection in the Iziko South African National Gallery: past, present and possible futures - Sanan, Sophia (Department of Sociology, 2025)
The Iziko South African National Gallery (ISANG) in Cape Town, which is South Africa's oldest 1 state art museum, began growing an African art collection (called the Permanent African Art Collection) in 1967. The collection today is cared for and owned by the Iziko Museums of South Africa Art Collections, or Iziko Art Collections. The very first artworks accessioned into the Permanent African Art Collection of the Iziko Museums of South Africa (from herewith the PAA collection), were a selection of West African figurative wooden sculptures purchased by assistant curator Bruce Arnott in 1967. The kinds of artworks subsequently placed in the PAA collection, hinged (mostly) on two implicit and contingent requirements: first that artworks were made by Africans but also that they expressed something about African ethnocentric traditions or histories. Hence, the PAA collection is ostensibly a historical collection, differentiated from contemporary and modern ‘African' artworks collected by the ISANG since 1964. The collection comprises largely of works by unknown artists, with many that have rough or vague attributions of time and place. By maintaining these implicit requirements, the collection points towards shifting notions of ‘tradition' and ‘history' regarding art from Africa, without expressly defining either of these terms. As such, this art collection, treated as a research site, presents a compelling starting point to unravel thorny questions around the historicisation of African art in a post-settler colonial context; the epistemic inheritances of art collections and the decolonial impulses that animate contemporary South African museum practice.